Visualizing information with Microsoft Office Visio 2007 [ smart diagrams for business users - Parker, David J. (McGraw Hill professional, 2007)
Helps learn the tools and features in Visio 2007. This title offers practical examples, reusable templates, and technical accuracy. It shows you how to get the most out of this data visualization application